Cyanobacterial Ecotypes in Different Optical Microenvironments of a 68°C Hot Spring Mat Community Revealed by 16S-23S rRNA Internal Transcribed Spacer Region Variation - Ferris, Mike J. (American Society for Microbiology, 2003)
We examined the population of unicellular cyanobacteria (Synechococcus) in the upper 3-mm vertical interval of a 68°C region of a microbial mat in a hot spring effluent channel (Yellowstone National Park, Wyoming). Fluorescence microscopy and microsensor measurements of O(2) and oxygenic photosynthesis demonstrated the existence of physiologically distinct Synechococcus populations at different depths along a light gradient quantified by scalar irradiance microprobes. Molecular methods were used to evaluate whether physiologically distinct populations could be correlated with genetically distinct populations over the vertical interval. We were unable to identify patterns in genetic variation in Synechococcus 16S rRNA sequences that correlate with different vertically distributed populations. However, patterns of variation at the internal transcribed spacer locus separating 16S and 23S rRNA genes suggested the existence of closely related but genetically distinct populations corresponding to different functional populations occurring at different depths.